Study of Spatial Pattern Suitability Based on Land System Data in Malang Regency and Malang City - Gafuraningtyas, Dewi; Indira; Musrah, Nur Auliya; Nurwadjedi (JURNAL GEOGRAFI, 2025)
The study objective is to describe the land characteristics of Malang Regency and Malang City and to evaluate the suitability of spatial patterns using data on the land system in these two locations. This study used spatial and descriptive analysis to discuss the land characteristics at the research site concerning land use as a cultivated area and protected area based on land system data and adjusted to the spatial plan, namely the Regional Spatial Plan (RTRW) of the research locations. There are 24 land systems data in Malang Regency and Malang City, six of which dominate, namely: Asembagus (ABG) 22.9%, Barong Tongkok (BTK) 16.9%, Tanggamus (TGM) 15.4%, Bukit Balang (BBG) 7.38%, Donomulyo (DML) 7%, and Muna (MNA) 6.8%. The results show that the spatial pattern contained in the RTRW map of Malang Regency and Malang City is suitable for the physical characteristics of the land.